Plasticity in male mating behavior modulates female life history in fruit flies. (21st January 2020) - Filice, David C. S.; Bhargava, Rajat; Dukas, Reuven
Abstract: In many species, intense male‐male competition for the opportunity to sire offspring has led to the evolution of selfish reproductive traits that are harmful to the females they mate with. In the fruit fly, Drosophila melanogaster, males modulate their reproductive behavior based on the perceived intensity of competition in their premating environment. Specifically, males housed with other males subsequently transfer a larger ejaculate during a longer mating compared to males housed alone. Although the potential fitness benefits to males from such plasticity are clear, its effects on females are mostly unknown. Hence, we tested the long‐term consequences to females from mating with males with distinct social experiences. First, we verified that competitive experience influences male mating behavior and found that males housed with rivals subsequently have shorter mating latencies and longer mating durations. Then, we exposed females every other day for 20 days to males that were either housed alone or with rivals, and subsequently measured their fitness. We found that females mated to males housed with rivals produce more offspring early in life but fewer offspring later in life and have shorter lifespans but similar intrinsic population growth rates. These results indicate that plasticity in male mating behavior can influence female life histories by altering females' relative allocation to early versus late investment in reproduction and survival.